The Place of The Mountain Area in Romanian Agriculture - Carmen CĂTUNĂ-BOCA; Vili DRAGOMIR; Gabriel POPESCU (Communications of International Proceedings, 2021)
Agriculture is a renewable resource that can be practiced for many generations to come. Romania must build its future by placing a strong emphasis on sustainable traditions. If we focus on temporary elements, these disappear completely after several years, and the solution is sustainable agriculture. The importance of mountain areas is also given by the territorial size. As at European level, they occupy a large territory in Romania: 30% of the country's surface.
Keywords: Romania; Mountain Area; Sustainable Agriculture.